Broadening the Concept of Marketing - Kotler, Philip; Levy, Sidney J. (Journal of Marketing, 1969)
Marketing is a pervasive societal activity that goes considerably beyond the selling of toothpaste, soap, and steel. The authors interpret the meaning of marketing for nonbusiness organizations and the nature of marketing functions such as product improvement, pricing, distribution, and communication in such organizations. The question considered is whether traditional marketing principles are transferable to the marketing of organizations, persons, and ideas.